Prevention of atrial fibrillation after cardiac surgery - Ronsoni, Rafael de March; Luz Leiria, Tiago Luiz; Silvestrini, Tiago Luiz; Martins, Leonardo Pires; Kruse, Marcelo Lapa; Gomes da Silva, Rogerio; Glotz de Lima, Gustavo (JOURNAL OF CARDIAC ARRHYTHMIAS, 2018)
Atrial fibrillation is the most commonly found arrhythmia after cardiac surgery. Although usually self-limiting, it represents an important predictor of increased patient morbidity, mortality, and health care costs. Numerous studies have attempted to determine the underlying mechanisms of postoperative atrial fibrillation with different results. A multifactorial pathophysiology is suggested, with inflammation and postoperative adrenergic activation recognized as important contributing factors. The management is complicated by a lack of data on the outcomes of different therapeutic interventions in this population. This article reviews the literature focusing on interventions to prevent postoperative atrial fibrillation.